Renal complications in chronic hypoparathyroidism – a systematic cross-sectional assessment - Gronemeyer, Karen; Fuss, Carmina Teresa; Hermes, Franca; Plass, Armin; Koschker, Ann-Cathrin; Hannemann, Anke; Völzke, Henry; Hahner, Stefanie (Frontiers in Endocrinology, 2023)
Context: Although renal long-term complications are acknowledged in chronic hypoparathyroidism (HPT), standardized investigations are scarce. Objective: To systematically investigate renal complications and their predictors in hypoparathyroid patients compared to matched individuals. Design: Prospective observational study in 161 patients with chronic HPT. Methods: Patients received renal ultrasound, clinical and laboratory assessments. An individual 1:3 matching with participants from the German population-based Study of Health in Pomerania was performed. Results: Of 161 patients (92% postoperative HPT), prevalence of eGFR <60ml/min/1.73m2 was 21%, hypercalciuria 41%. Compared to healthy individuals, HPT patients had a significantly lower eGFR (74.2 vs. 95.7 ml/min/1.73m², p<0.01). Renal ultrasound revealed calcifications in 10% (nephrocalcinosis in 7% and calculi in 3%). Patients with renal calcifications had higher levels of 24-hour urine calcium excretion (8.34 vs. 5.08 mmol/d, p=0.02), spot urine calcium excretion (4.57 vs. 2.01 mmol/L, p=0.01) and urine calcium-to-creatinine ratio (0.25 vs. 0.16, p<0.01) than patients without calcifications. Albumin-corrected calcium, phosphate, calcium-phosphate product, 25-hydroxyvitamin D in serum, eGFR, daily calcium intake or disease duration were not significantly different between these two groups. Including patients receiving rhPTH therapy, a lower serum phosphate concentration (odds ratio 1.364 [95% confidence interval (CI) 1.049-1.776], p<0.05) and a longer disease duration of HPT (odds ratio 1.063 [95% CI 1.021-1.106], p<0.01) were significant predictors for renal calcifications. Excluding patients receiving rhPTH therapy, a higher 24-hour urine calcium excretion (odds ratio 1.215 [95% CI 1.058-1.396], p<0.01) was a significant predictor for renal calcifications but not serum magnesium or disease duration. Conclusions: Prevalence of impaired renal function among patients with chronic HPT is increased and independent from visible renal calcifications. Depending on exclusion of patients with rhPTH therapy, regression analysis revealed disease duration and serum phosphate or disease duration and 24-hour urinary calcium excretion as predictors for renal calcifications. Clin Trials Identifier: NCT05585593